Respiratory Symptoms of Vendors in an Open-Air Hawker Center in Brunei Darussalam - Nazurah bt Abdul Wahid, Nurul Nor; Balalla, N. B. P; Koh, David (Frontiers in Public Health, 2014)
Objectives We studied respiratory problems among vendors exposed to cooking fumes in an open-air hawker centre. Exposure to cooking fumes from either the use of fossil fuels or liquefied petroleum gas (LPG) has been shown to be associated with adverse respiratory health effects. Methods We conducted a cross-sectional study among 67 food vendors exposed to cooking fumes as well as 18 merchandise sellers at an open-air hawker centre in Brunei Darussalam. Past medical and smoking history and exposure to cooking fumes were obtained. The validated American Thoracic Society (ATS) Questionnaire with a translated Malay version was used to ask for respiratory symptoms. Results Compared to merchandise sellers (n=18), cooking vendors (n=67) had a higher self-reported respiratory symptoms (50.7% for those cooking and 33.3% for merchandise sellers). Cough (28.3%) was the main respiratory symptom experienced in cooking vendors and breathlessness (22.2%) among merchandise sellers. Half (50.0%) of cooking vendors who worked for more than 10 years had cough and 27.3% had phlegm. Those cooking with charcoal were two times more likely to have cough than those cooking with LPG. Cooking vendors with a job duration of more than 10 years were thrice more likely to have cough. Conclusion Cooking vendors in the open air hawker centre exposed to cooking fumes had more respiratory symptoms compared to non-exposed merchandise sellers. The type of fuel used for cooking and duration of work were associated with increased prevalence of cough.